Effect of a short-term HAART on SIV load in macaque tissues is dependent on time of initiation and antiviral diffusion - Durand-Gasselin Lucie; Roucairol Camille; Sellier Pierre; Mannioui Abdelkrim; Bourry Olivier; Dereuddre-Bosquet Nathalie; Benech Henri; Roques Pierre; Le Grand Roger (Retrovirology, 2010)
Abstract Background HIV reservoirs are rapidly established after infection, and the effect of HAART initiated very early during acute infection on HIV reservoirs remains poorly documented, particularly in tissue known to actively replicate the virus. In this context, we used the model of experimental infection of macaques with pathogenic SIV to assess in different tissues: (i) the effect of a short term HAART initiated at different stages during acute infection on viral dissemination and replication, and (ii) the local concentration of antiviral drugs. Results Here, we show that early treatment with AZT/3TC/IDV initiated either within 4 hours after intravenous infection of macaques with SIVmac251 (as a post exposure prophylaxis) or before viremia peak (7 days post-infection [pi]), had a strong impact on SIV production and dissemination in all tissues but did not prevent infection. When treatment was initiated after the viremia peak (14 days pi) or during early chronic infection (150 days pi), significant viral replication persists in the peripheral lymph nodes and the spleen of treated macaques despite a strong effect of treatment on viremia and gut associated lymphoid tissues. In these animals, the level of virus persistence in tissues was inversely correlated with local concentrations of 3TC: high concentrations of 3TC were measured in the gut whereas low concentrations were observed in the secondary lymphoid tissues. IDV, like 3TC, showed much higher concentration in the colon than in the spleen. AZT concentration was below the quantification threshold in all tissues studied. Conclusions Our results suggest that limited antiviral drug diffusion in secondary lymphoid tissues may allow persistent viral replication in these tissues and could represent an obstacle to HIV prevention and eradication.